Islamic Education and Generation Z Moral Development: Digital-Based Character Building in Indonesian Urban Schools - Ushie Uswatun Hasanah; Muh. Asharif Suleman; Sayed Sayed; Zulfi Idayanti; Ahmad Hilmi; Muh Zacky Fadhil Rachmat (Journal of Contemporary Islamic Primary Education, 2025)
Despite extensive research on moral education, limited studies examine how Islamic education responds to Generation Z’s moral crisis amid Indonesia’s rapid digital transformation. This study explores the role of Islamic education in fostering moral resilience among urban Generation Z facing digital globalization challenges. Using a qualitative descriptive case study, data were collected through in-depth interviews with 15 Islamic Religious Education teachers, 5 school principals, and 30 students from five urban Islamic schools implementing digital-integrated learning. Data were supported by 120 hours of participatory observation and document analysis over six months. Findings identify five major manifestations of moral crisis: declining social empathy, with 62% of students prioritizing virtual over real interactions; exposure to harmful digital content affecting 87% of students; digital hedonism influencing 77%; rising individualism, with 68% preferring individual tasks; and weakened spiritual awareness reflected in a 60% decline in voluntary religious participation. Islamic education shows strategic potential through digital media integration, project-based learning that achieved 85% student engagement, and teacher digital role modeling. However, challenges persist, including limited educator digital literacy (68% lacking adequate training), non-contextual pedagogy in 60% of observed classes, and weak family–school collaboration. This study proposes a transformative framework integrating Islamic values with digital pedagogy for Indonesian Generation Z, contributing to SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities) through culturally responsive moral education.